SAS certification prep guide statistical business analysis using SAS9 - Shreve, Joni N. (SAS Institute, 2018)
Must-have study guide for the SAS® Certified Statistical Business Analyst Using SAS®9: Regression and Modeling exam! Written for both new and experienced SAS programmers, the SAS® Certification Prep Guide: Statistical Business Analysis Using SAS®9 is an in-depth prep guide for the SAS® Certified Statistical Business Analyst Using SAS®9: Regression and Modeling exam. The authors step through identifying the business question, generating results with SAS, and interpreting the output in a business context. The case study approach uses both real and simulated data to master the content of the cert.
Key Words for Generating Desired Statistics. - Includes bibliographical references. - Print version record
Keywords: SAS (Computer file); SAS (Computer program language); Electronic data processing personnel -- Study guides -- Certification; SAS (Langage de programmation); COMPUTERS; Programming Languages; General; Electronic data processing personnel; Certification; Study guides